Question
upstudy study bank question image url

The graph of \( g(x)=a\left(\frac{1}{5}\right)^{x}-5 \) passes throunti \( (-2 ;-4) \). 7.1 Show that \( \alpha=\frac{1}{25} \) 7.2 Determine the coordinates of the \( x \) intericentof 7.3 Given: \( h(x)=\left(\frac{1}{5}\right)^{x} \) 7.3.1 Determine the equation of \( x^{-1}(x) \), the inverse of \( h \), in the for \( y=\ldots \) 7.3.2 Describe the transformation from. g to h .

Ask by Weber Chen. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

7.1 \( \alpha = \frac{1}{25} \) 7.2 The \( x \)-intercept is at \( (3, 0) \). 7.3.1 The inverse of \( h(x) \) is \( y = -\log_{5}(x) \). 7.3.2 The transformation from \( g(x) \) to \( h(x) \) involves a vertical compression by a factor of \( \frac{1}{25} \) and a downward shift of 5 units.

Solution

Let's solve the problem step by step. ### 7.1 Show that \( \alpha = \frac{1}{25} \) We know that the graph of \( g(x) = a\left(\frac{1}{5}\right)^{x} - 5 \) passes through the point \( (-2, -4) \). This means that when \( x = -2 \), \( g(-2) = -4 \). Substituting \( x = -2 \) into the equation: \[ g(-2) = a\left(\frac{1}{5}\right)^{-2} - 5 = -4 \] Calculating \( \left(\frac{1}{5}\right)^{-2} \): \[ \left(\frac{1}{5}\right)^{-2} = 5^2 = 25 \] Now substituting this back into the equation: \[ g(-2) = a \cdot 25 - 5 = -4 \] Rearranging gives: \[ a \cdot 25 = -4 + 5 \] \[ a \cdot 25 = 1 \] \[ a = \frac{1}{25} \] Thus, we have shown that \( \alpha = \frac{1}{25} \). ### 7.2 Determine the coordinates of the \( x \)-intercept The \( x \)-intercept occurs when \( g(x) = 0 \). We can set the equation to zero and solve for \( x \): \[ 0 = \frac{1}{25}\left(\frac{1}{5}\right)^{x} - 5 \] Rearranging gives: \[ \frac{1}{25}\left(\frac{1}{5}\right)^{x} = 5 \] Multiplying both sides by 25: \[ \left(\frac{1}{5}\right)^{x} = 125 \] Since \( 125 = 5^3 \), we can rewrite this as: \[ \left(\frac{1}{5}\right)^{x} = 5^{-3} \] This implies: \[ -x = -3 \quad \Rightarrow \quad x = 3 \] Thus, the coordinates of the \( x \)-intercept are \( (3, 0) \). ### 7.3 Given: \( h(x) = \left(\frac{1}{5}\right)^{x} \) #### 7.3.1 Determine the equation of \( x^{-1}(x) \), the inverse of \( h \) To find the inverse of \( h(x) \), we start with: \[ y = \left(\frac{1}{5}\right)^{x} \] Now, we solve for \( x \): 1. Take the logarithm of both sides: \[ \log(y) = x \log\left(\frac{1}{5}\right) \] 2. Rearranging gives: \[ x = \frac{\log(y)}{\log\left(\frac{1}{5}\right)} \] Thus, the inverse function is: \[ x^{-1}(y) = \frac{\log(y)}{\log\left(\frac{1}{5}\right)} \] In terms of \( y \): \[ y = \left(\frac{1}{5}\right)^{x} \quad \Rightarrow \quad x = -\log_{5}(y) \] So, the equation of the inverse is: \[ y = -\log_{5}(x) \] #### 7.3.2 Describe the transformation from \( g \) to \( h \) The transformation from \( g(x) \) to \( h(x) \) can be described as follows: 1. **Vertical Stretch/Compression**: The function \( g(x) \) is vertically compressed by a factor of \( \frac{1}{25} \) compared to \( h(x) \). 2. **Vertical Shift**: The function \( g(x) \) is shifted down by 5 units compared to \( h(x) \). In summary, the transformation from \( h(x) \) to \( g(x) \) involves a vertical compression by a factor of \( \frac{1}{25} \) and a downward shift of 5 units.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find \( \alpha \), we can use the point \( (-2, -4) \). Plugging in these values into the equation \( g(x) = a\left(\frac{1}{5}\right)^{x}-5 \): \[ -4 = a\left(\frac{1}{5}\right)^{-2} - 5 \] Solving for \( a \): \[ -4 + 5 = a(25) \] \[ 1 = 25a \Rightarrow a = \frac{1}{25} \] Thus, \( \alpha = \frac{1}{25} \). For the \( x \)-intercept, set \( g(x) = 0 \): \[ 0 = a\left(\frac{1}{5}\right)^{x} - 5 \] Solving gives: \[ a\left(\frac{1}{5}\right)^{x} = 5 \Rightarrow \left(\frac{1}{5}\right)^{x} = 125 \Rightarrow \left(\frac{1}{5}\right)^{x} = \left(\frac{1}{5}\right)^{-3} \] Thus, \( x = -3 \). The coordinates are \( (-3, 0) \). To find the inverse \( h^{-1}(x) \): Let \( y = \left(\frac{1}{5}\right)^{x} \): \[ x = \left(\frac{1}{5}\right)^{y} \Rightarrow \log_{(1/5)}(x) = y \] In exponential form, it becomes \( y = -\log_{5}(x) \). For the transformation from \( g \) to \( h \): We can see that \( g(x) \) is a transformation of \( h(x) \) which includes vertical scaling by \( a \) (a factor of \( \frac{1}{25} \)), a horizontal translation (shifting left or right, defined by the \( x \)-intercept), and a vertical shift downward by 5. So, it’s like taking our \( h(x) \) and shrinking it while also shifting it down!

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy